2018
DOI: 10.5812/amh.85275
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E As an Antioxidant Reduces Apoptosis of Cells in Rat Hippocampus Following Exposure to Polyvinyl Chloride

Abstract: Background: Many studies have shown that polyvinyl chloride (PVC) has toxic effects on the body and brain. Vitamin E is a nutritional supplement that acts as an antioxidant, scavenging toxic free radicals. Objectives: The aim of this study was to examine the protective effects of vitamin E against PVC-induced damages in rat hippocampus. Methods: In this study, 24 male Wistar rats were randomly divided to four groups (n = 6), including control, vitamin E (150 mg/kg.bw/day), PVC (1000 mg/kg.bw/day), PVC + vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Besides, it inhibits DNA damage and neural apoptosis [ 83 ]. In addition, it diminishes the apoptosis of cells in the rat hippocampus after polyvinyl chloride exposure [ 84 ]. Vitamin C is also useful in modulating oxidative stress, autophagy, and apoptosis in bone marrow stromal cells [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it inhibits DNA damage and neural apoptosis [ 83 ]. In addition, it diminishes the apoptosis of cells in the rat hippocampus after polyvinyl chloride exposure [ 84 ]. Vitamin C is also useful in modulating oxidative stress, autophagy, and apoptosis in bone marrow stromal cells [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…We orally administered vitamin E (150 mg/kg.bw/day) and PVC (1000 mg/kg.bw/day) for 40 days. The PVC (Merck, Germany) and vitamin E were used as described in previous studies (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…Research results have shown that PVC contributes to some neurodegenerative diseases. Vitamin E is one of the most important antioxidants that can prevent damaging effects leading to a number of diseases, such as diabetes (11)(12)(13), stroke (14,15), Alzheimer (16,17), and aging (18).…”
Section: Introductionmentioning
confidence: 99%